Problems of Students' Mathematical Literacy Reviewed from the Self-Regulated Learning of Vocational High School Students on Exponential Material - Pratiwi, Yolanda; Kusno, Kusno; Subekti, Fitrianto Eko (Proceedings Series on Social Sciences & Humanities, 2025)
Mathematical literacy is a crucial aspect of mathematics learning, yet it remains a significant challenge among students. While previous research has largely emphasized instructional approaches to enhance mathematical literacy, there is a lack of focus on the underlying difficulties faced by students, particularly in relation to self-regulated learning (SRL). This study aims to explore the problems in mathematical literacy encountered by vocational high school students at SMK Negeri 2 Bawang, Banjarnegara Regency, on exponential material, analyzed through their SRL levels. Employing a descriptive qualitative approach, the study involved three student subjects representing high, medium, and low SRL categories. Data collection was conducted using a mathematical literacy test, an SRL questionnaire, and interviews. The results indicate that variations in SRL levels significantly influence the types of difficulties students experience. Students with low SRL face extensive challenges, including understanding problem contexts, constructing mathematical models, and interpreting results. Those with medium SRL can comprehend the problems but struggle with selecting appropriate solution strategies and accurately representing contextual situations in mathematical forms. Meanwhile, students with high SRL exhibit systematic and reflective thinking yet encounter obstacles in connecting mathematical results to real-life contexts. These findings underscore the role of SRL in shaping students' mathematical literacy challenges. Further research is recommended to investigate additional internal factors affecting mathematical literacy to develop more adaptive and targeted instructional strategies.